2007
DOI: 10.1038/sj.leu.2404727
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a quantitative PCR method with FISH for the assessment of the four aneuploidies commonly evaluated in CLL patients

Abstract: Four chromosomal defects associated with outcome are commonly evaluated by fluorescent in situ hybridization (FISH) in chronic lymphocytic leukemia (CLL), namely deletions of the 13q13-q14, 11q22 and 17p13 regions and trisomy 12. In this study, we compared a quantitative PCR method -quantitative multiplex PCR of short fluorescent fragment (QMPSF) -with FISH for the detection of these acquired aneuploidies in a series of 110 patients with Binet stage A CLL. Genes located in the deleted or gained regions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…11 Briefly, QMPSF is a sensitive method for the detection of genomic deletions or duplications based on the simultaneous amplification of short genomic fragments using dye-labelled primers under quantitative conditions. PCR products were analysed on an ABI Prism310 genetic analyser in the fragment analysis mode, in which both peak heights and areas are proportional to the quantity of template present for each target sequence.…”
Section: Breakpoint Mapping and Real-time Quantitative Reverse-transcmentioning
confidence: 99%
“…11 Briefly, QMPSF is a sensitive method for the detection of genomic deletions or duplications based on the simultaneous amplification of short genomic fragments using dye-labelled primers under quantitative conditions. PCR products were analysed on an ABI Prism310 genetic analyser in the fragment analysis mode, in which both peak heights and areas are proportional to the quantity of template present for each target sequence.…”
Section: Breakpoint Mapping and Real-time Quantitative Reverse-transcmentioning
confidence: 99%
“…Using this approach, we demonstrated that TP53 and MDM2 somatic defects could be reliably detected when the proportion of tumoral cells was as low as 20%. 15 In addition, polymorphic gene copy number changes were excluded in some cases using matched non-tumoral DNA as control.…”
Section: Qmpsf Assaymentioning
confidence: 99%
“…By contrast, quantitative multiplex polymerase chain reaction of short fluorescent fragments (QMPSF) is an inexpensive and sensitive method for the detection of genomic deletions or duplications based on the simultaneous amplification of short genomic fragments using dye-labeled primers under quantitative conditions. [13][14][15] Using this approach, we determined gain/loss frequencies of several targeted genes and built a biological score able to predict the outcome of DLBCL independently of the International Prognostic Index.…”
Section: Introductionmentioning
confidence: 99%
“…11 We previously demonstrated its applicability to the analysis of various hematologic neoplasms, including chronic lymphocytic leukemia (CLL), DLBCL, mantle cell lymphoma (MCL), and CD4 ϩ CD56 ϩ hematodermic neoplasms. [12][13][14][15] We also assessed its prognostic relevance and its feasibility using formalin-fixed paraffin-embedded (FFPE) tissues in MCL. 13 Here, we assess the prognostic value of GCNA (TP53, CDKN2A, REL, BCL2, MYC, and RB1) detected by QMPSF in DLBCL, in a setting of clinical trials based on the use of R-CHOP or R-CHOPlike regimens.…”
Section: Introductionmentioning
confidence: 99%